A Neural Network for Common Due Date Job Scheduling Problem on Parallel Unrelated Machines - Hamad, Abdelaziz; Sanugi, Bahrom; Salleh, Shaharuddin (Faculty of Science, Universiti Teknologi Malaysia, 2001)
This paper presents an approach for scheduling under a common due date on parallel unrelated machine problems based on artificial neural network. The objective is to allocate and sequence the jobs on the machines so that the total cost be minimized. This cost is composed of the total earliness and the total tardiness cost. Neural network is a suitable model in our study due to the fact that the problem is NP-hard. In our study, neural network has been proven to be effective and robust in generating near optimal solutions to the problem.